Law Enforcement of Cybercrime: Tracking Digital Footprints of Cross-Border Hackers - Nusa, Idham Qrida; Sugiri, Bambang; Yuliati, Yuliati; Sulistio, Faizin (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2025)
This journal analyzes the procedural criminal law (KUHAP) in dealing with cybercrime within formal legal law. The analysis highlights the use of cloud storage as a media to store the proceeds of crime, in the form of data privacy. As a case study to show how cyber criminals commit cyber crimes by using computer networks, investigators still face difficulties in conducting searches and seizures to obtain evidence. The results of data theft crimes which are stored in cloud storage, make digital evidence difficult to be seized, nothing can be used as evidence. As a result, digital evidence from crimes remains accessible and can be reused in subsequent crime, while, hackers remain uncaptured. What strategies can the Indonesian government implement to overcome and prevent cyberbcrime attacks in the future? This requires reformulating legal provisions as amendments and improvements to Law Number 8 of 1981 concerning the Indonesian Criminal Procedure Code (KUHAP), with reference to the Budapest Convention. This research examines the main problem using a normative juridical approach, statutory approach, case approach, and comparative legal methods, combined with qualitative analysis approach. It philosophically examines the principle of legal certainty and analyzes legal theories of punishment and confiscation. Thus, a formal procedural legal system is applied to regulate the seizure and search of intangible electronic, enabling the electronic evidence stored in cloud to be seized or taken down from cyberspace, declared valid in court, fulfilling the principle of legal certainty to trace the footsteps of hackers across countries/internationally.